The Role of Hexagon Fraud in Detecting the Occurrence of Restatements by Moderating Audit Quality (Empirical Study on the Healthcare Sector Listed on the Indonesia Stock Exchange for the Period 2020 - 2022) - Fauzia, Rizka; Rani, Puspita (Journal Research of Social Science, Economics, and Management, 2025)
This study aims to analyze the effects of pressure, opportunity, rationalization, capability, arrogance dan collusion on restatement with audit quality as the moderating variable. The study was conducted on healthcare sector companies listed on the Indonesian Stock Exchange in 2020-2022. The sample was selected using purposive sampling, and the data that passed the selection process consisted of 13 companies. The results show that pressure, opportunity, rationalization, capability, arrogance dan collusion have no significant effects on restatement. Additionally, audit quality as the moderating variable can not moderate pressure, opportunity, rationalization, capability, arrogance dan collusion in relation to restatement.